Visages du Brésil méridional : l´immigration polonaise et italienne au Paraná entre la fin du XIXe et le début du XXe siècle - Márcio de Oliveira (Confins)
The immigration to Brazil has been studied in a general and national ways. Some data show that the process happened, mainly, in Southern Brazil, that means, most of the immigration was destined to the states of São Paulo, Paraná, Santa Catarina and Rio Grande do Sul. This paper analyses the Polish and Italian immigration processes to the state of Paraná, located in Southern Brazil. Polish organizations in Paraná are several and varied. They go from schools to sports associations and even press means which contradicts the courant notion of Polishes illiterates. The variety was such that creating a colony of the Republic of Poland in Paraná was even considered and discussed about. The Italians in Paraná were not so numerically important, though they were as equally active within the local society. Italians have shown great vitality in their own cultural organizations in Curitiba, capital city of Paraná, and inside the surrounding colonies so that the consequences of their actions are still recognizable in current times.